Can malocclusion provide clinicians with information for differential diagnosis of temporomandibular joint diseases?: A review. Issue 33 (19th August 2022) - Matsuda, Shinpei; Yamaguchi, Taihiko; Mikami, Saki; Yoshimura, Hitoshi; Gotouda, Akihito
Abstract : The aim of this literature review was to summarize the clinical characteristics and symptoms of temporomandibular joint diseases, and to discuss the associations between temporomandibular joint diseases and categorization of malocclusion. Electronic literature searches were performed using the PubMed database. The authors established a differential diagnostic method for temporomandibular joint diseases related to malocclusion. A literature search using PubMed yielded 213 texts, of which based on exclusion criteria, 28 were included in this study. Malocclusions were categorized into 5 types. The authors suggested a diagnostic tree of temporomandibular joint diseases based on the types of malocclusion and 4 variables in clinical characteristics and symptoms. Clinicians treating malocclusions must attempt to clarify the cause of the occlusal condition. If caused by temporomandibular joint disease, it is important to make a proper differential diagnosis at first, and not to overlook the causative disease. Further clinical knowledge of associations between temporomandibular joint diseases and malocclusions should be accumulated, and the diagnostic tree should be improved based on new information.